The Malleus Maleficarum and the construction of witchcraft : theology and popular belief - Broedel, Hans Peter (Studies in early modern European history., 2003)
What was witchcraft? Were witches real? How should witches be identified? How should they be judged? Towards the end of the middle ages these were serious and important questions - and completely new. Between 1430 and 1500, a number of learned 'witch-